PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN JASMANI DI SMPN 1 KALASAN, SLEMAN - Ahmad Rithaudin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
This action research was aimed to improve the learning quality of the physical education by using the audiovisual media in SMPN 1 Kalasan, Sleman in the academic year of 2005-2006. The subject of the research was the students of grade VII D SMPN 1 Kalasan. The number of the students was 38 students, consisted of 17 male and 21 female in the academic year of 2005-2006. The subject matter of learning is shooting in basket ball. The techniques of the data collection of the research were questionnaire, interview, and observation, while the technique of the data analysis of the research was descriptive. The result of research showed that implementation of audiovisual media by DVD can improve the students appreciation in learning as well as enhance the students learning performance. The suggestions to be considered are the need of implementing the audiovisual as media learning in large scope and different subject matter. The school needs special class for audiovisual media. Kata kunci: media audiovisual, metode pembelajaran